Huge hemorrhagic ovarian cyst alongside suspected ovarian torsion: a case report - Sindan, Namita; Bhandari, Adheesh (Journal of Patan Academy of Health Sciences, 2020)
An ovarian cyst is usually a relatively large, fluid-filled cystic structure (diameter greater than 3 cm) that originates from the surface or inside the ovary. Ovarian cysts can be simple or complex, depending on their internal material. Hemorrhagic ovarian cysts (HOCs) are commonly seen in clinical practice. Most of them resolve naturally during follow-up except in a minority of cases in which surgical intervention is needed. Ovarian torsion indicates partial or complete rotation of the ovary and a portion of the fallopian tube along its supplying vascular pedicle. It usually occurs in the reproductive age group, more on the right side (about 60%), and often presents with acute lower abdominal pain lasting for a few hours to 24 hours. It is one of the harmful conditions, hampering blood supply of ovary which may rise to overall necrosis of ovarian tissue and other difficulties, if not identified and managed in time. We present a case of a huge hemorrhagic ovarian cyst managed in the Department of Gynecology and Obstetrics, Paropakar Maternity and Women’s Hospital, Kathmandu, Nepal.